Kinematics of cross-country ski racing - Bilodeau, B.; Rundell, K. W.; Roy, B.; Boulay, M. R. (Medicine & Science in Sports & Exercise, 1996)
This study investigated the evolution of skiing velocity, cycle length, and cycle rate in elite and subelite skiers during cross-country ski races. Senior male cross-country skiers engaged respectively in a 30-km skating race (N = 34) or a 50-km classical race (N = 27) were videotaped as they skied two different sections of 30 m, a 7 degrees uphill, and a flat section. In the skating race, most skiers used the offset technique on uphill and the 2-skate on flat, while the preferred techniques during the classical race were the diagonal stride for uphill and double-poling on flat. Results demonstrated that faster skiers had longer cycle lengths than slower skiers except for the flat sections of the classical race. Cycle rate was not different between skiers of different performance levels in any circumstances or races. Decreased velocity observed during the second half of the skating race was almost entirely due to a decrease in cycle length. We conclude that slower athletes should emphasize extending cycle length during their technical training. Therefore, skiers should place an emphasis on strength and power training to increase their kick and pole pushes and enhance cycle length.